2019
DOI: 10.1111/dom.13616
|View full text |Cite
|
Sign up to set email alerts
|

A comparative effectiveness study of degludec and insulin glargine 300 U/mL in insulin‐naïve patients with type 2 diabetes

Abstract: Aims To compare the real‐world effectiveness of insulin degludec (degludec) and glargine 300 units/mL (glargine U300) in insulin‐naïve adult patients with type 2 diabetes in routine US clinical practice. Materials and methods CONFIRM is a non‐interventional comparative effectiveness study following US patients across the continuum of care, through electronic medical records from multiple health systems and integrated delivery networks. Propensity‐score matching controlled for confounding. The primary endpoint,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
3
52
1
4
Order By: Relevance
“…Although the results from the current study are consistent with data from the BRIGHT trial in insulin‐naïve adults with T2D and the three previous real‐world studies in insulin‐naïve or ‐experienced adults with T2D, there are some interesting differences between the insulin‐naïve studies. Firstly, patients in the current study had considerably higher mean baseline HbA1c values than those in the BRIGHT trial [9.7% vs. 8.6% (83 vs. 71 mmol/mol, respectively)].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the results from the current study are consistent with data from the BRIGHT trial in insulin‐naïve adults with T2D and the three previous real‐world studies in insulin‐naïve or ‐experienced adults with T2D, there are some interesting differences between the insulin‐naïve studies. Firstly, patients in the current study had considerably higher mean baseline HbA1c values than those in the BRIGHT trial [9.7% vs. 8.6% (83 vs. 71 mmol/mol, respectively)].…”
Section: Discussionsupporting
confidence: 87%
“…The CONFIRM study examined the EMRs of insulin-naïve adults with T2D from the same database as the current study (Explorys; IBM Watson Health), but reported that IDeg was associated with a significantly larger mean HbA1c reduction and significantly greater "reductions in the change in the likelihood of hypoglycaemia" than Gla-300. 17 The CONFIRM findings, however, appear to be the consequence of methodological dif- there may also be baseline imbalances here too, perhaps providing an explanation for the CONFIRM study's deviation from the current evidence base. Finally, it is worth noting that the CONFIRM population appears to have a pattern of baseline medication that is inconsistent with what might be expected for an insulin-naïve cohort.…”
Section: All Patients Switched Frommentioning
confidence: 80%
“…Tibaldi et al report results of the propensity‐matched observational CONFIRM study in previously insulin‐naïve adults with type 2 diabetes, comparing two second‐generation basal insulins. Using patients' electronic medical records from a large US database, they report an association between treatment with insulin degludec (IDeg) and a reduction in glycated haemoglobin (HbA1c) and hypoglycaemia rates, compared with insulin glargine 300 units/mL (Gla‐300).…”
mentioning
confidence: 99%
“…No significant between‐treatment differences in hypoglycaemia incidence or rates (hospitalizations or ED visits) were observed between Gla‐300 or IDeg following adjustment for baseline hypoglycaemia . By contrast, CONFIRM showed significantly greater HbA1c reductions with IDeg than Gla‐300 (−1.48% vs. −1.22%; P = 0.03) . Similarly, over the initial 180 days, the proportion of patients experiencing ≥1 hypoglycaemic event was significantly lower with IDeg than Gla‐300 ( P <0.01) and fewer patients discontinued treatment with IDeg than Gla‐300 (13% vs. 21%; P <0.001) …”
Section: Can Newer Bi Analogues Assist With Insulin Titration and Trementioning
confidence: 91%
“…Real‐world studies comparing first‐ and second‐generation BIs using electronic health record data have also been conducted. The CONFIRM and DELIVER‐D+ studies compared HbA1c reduction and hypoglycaemia risk in US patient records for individuals using either Gla‐300 or IDeg, with both studies using propensity score matching (PSM) to account for potential confounders; however, these studies showed conflicting results . DELIVER‐D+ showed similar HbA1c reductions (Gla‐300: 0.63 [SD 1.7]%, IDeg‐100: 0.58 [1.6]%; P = 0.488) and HbA1c <7% target achievement (Gla‐300: 15.1%, IDeg: 16.1%; P = 0.628) from baseline to 3–6 months’ follow‐up .…”
Section: Can Newer Bi Analogues Assist With Insulin Titration and Trementioning
confidence: 99%